Added Diagnostic Value of Cerebrospinal Fluid Biomarkers for Differential Dementia Diagnosis in an Autopsy-Confirmed Cohort. - Niemantsverdriet, Ellis; Feyen, Bart F E; Le Bastard, Nathalie; Martin, Jean-Jacques; Goeman, Johan; De Deyn, Peter Paul; Bjerke, Maria; Engelborghs, Sebastiaan (J Alzheimers Dis, 2018)
BACKGROUND: Differential dementia diagnosis remains a challenge due to overlap of clinical profiles, which often results in diagnostic doubt. OBJECTIVE: Determine the added diagnostic value of cerebrospinal fluid (CSF) biomarkers for differential dementia diagnosis as compared to autopsy-confirmed diagnosis. METHODS: Seventy-one dementia patients with autopsy-confirmed diagnoses were included in this study. All neuropathological diagnoses were established according to standard neuropathological criteria and consisted of Alzheimer's disease (AD) or other dementias (NONAD). CSF levels of Aβ1 - 42, T-tau, and P-tau181 were determined and interpreted based on the IWG-2 and NIA-AA criteria, separately. A panel of three neurologists experienced with dementia made clinical consensus dementia diagnoses. Clinical and CSF biomarker diagnoses were compared to the autopsy-confirmed diagnoses. RESULTS: Forty-two patients (59%) had autopsy-confirmed AD, whereas 29 patients (41%) had autopsy-confirmed NONAD. Of the 24 patients with an ambiguous clinical dementia diagnosis, a correct diagnosis would have been established in 67% of the cases applying CSF biomarkers in the context of the IWG-2 or the NIA-AA criteria respectively. CONCLUSION: AD CSF biomarkers have an added diagnostic value in differential dementia diagnosis and can help establishing a correct dementia diagnosis in case of ambiguous clinical dementia diagnoses.